2016
DOI: 10.3389/fphar.2016.00492
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Enhancing-Memory Effect of Donepezil and S 38093 (a Histamine H3 Antagonist) Is Mediated by Increased Neural Activity in the Septo-hippocampal Circuitry in Middle-Aged Mice

Abstract: Donepezil, an acetylcholinesterase inhibitor, induces only moderate symptomatic effects on memory in Alzheimer’s disease patients. An alternative strategy for treatment of cognitive symptoms could be to act simultaneously on both histaminergic and cholinergic pathways, to create a synergistic effect. To that aim, 14 month old C57/Bl6 mice were administered per oesophagy during nine consecutive days with Donepezil (at 0.1 and 0.3 mg/kg) and S 38093 (at 0.1, 0.3, and 1.0 mg/kg), a H3 histaminergic antagonist dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The doses were several-fold lower than the dose that mediated the functional effects at H3 receptor. S 38093 also potentiated the procognitive effects of donepezil (Sors et al, 2016). The observed effects of S 38093 may also have been mediated through the sigma-1 receptors (see above).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The doses were several-fold lower than the dose that mediated the functional effects at H3 receptor. S 38093 also potentiated the procognitive effects of donepezil (Sors et al, 2016). The observed effects of S 38093 may also have been mediated through the sigma-1 receptors (see above).…”
Section: Discussionmentioning
confidence: 97%
“…JNJ-10181457 significantly attenuated the scopolamine-induced memory deficits in delayed non-matching to position task in rats (Galici et al, 2009). In a contextual serial discrimination task, S 38093 significantly reversed the memory deficits associated with ageing, and further a synergistic effect on cognition was observed when co-administered with donepezil in mice (Panayi et al, 2017;Sors et al, 2016). Ciproxifan attenuated the memory deficits caused by chronic restraint stress in object recognition and passive avoidance tasks in rats (Trofimiuk and Braszko, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…However, we found that the injection of rolipram in the presence of HIV-1 gp120 restored memory. Donepezil, a CREB inducer, also restored memory (data not shown) (47). Brains were collected from these mice and protein extracts were isolated from the hippocampal area and then subjected to western blot analysis.…”
Section: Evidence That Rolipram Restored Memory In Micementioning
confidence: 87%
“…Based on these results, we conducted MWM test on animals at the late stage of dementia to compare cognitive abilities between the two groups [40]. In the SIP3L co-treatment group, the time to reach the target quadrant was shorter and the time spent in the target quadrant was longer, indicating that the animals in this group had a more improved cognitive ability than those treated with donepezil alone [41,42].…”
Section: Discussionmentioning
confidence: 99%